2013
DOI: 10.1007/s00428-013-1486-1
|View full text |Cite
|
Sign up to set email alerts
|

Reliable PCR quantitation of estrogen, progesterone and ERBB2 receptor mRNA from formalin-fixed, paraffin-embedded tissue is independent of prior macro-dissection

Abstract: Gene expression analysis on messenger RNA (mRNA) purified from formalin-fixed, paraffin-embedded tissue is increasingly used for research purposes. Tissue heterogeneity may question specificity and interpretation of results from mRNA isolated from a whole slide section, and thresholds for minimal tumor content in the paraffin block or macrodissection are used to avoid contamination from non-neoplastic tissue. The aim was to test if mRNA from tissue surrounding breast cancer affected quantification of estrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…In the respective experiments, we found that changes in the relative gene expression were insignificant down to 20–39% TCC. This is in agreement with data reported by Tramm and coworkers, who showed an excellent agreement between gene expression data for ESR1, PGR and ERBB2 from whole tissue and from macrodissected extracts [ 30 ]. Likewise, macrodissection did not affect the prognostic significance of RNA expression of cancer-associated genes in primary breast tumor samples [ 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the respective experiments, we found that changes in the relative gene expression were insignificant down to 20–39% TCC. This is in agreement with data reported by Tramm and coworkers, who showed an excellent agreement between gene expression data for ESR1, PGR and ERBB2 from whole tissue and from macrodissected extracts [ 30 ]. Likewise, macrodissection did not affect the prognostic significance of RNA expression of cancer-associated genes in primary breast tumor samples [ 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that the relative gene expression of the analyzed genes is even preserved in samples with a TCC below 30 %. Similar results were obtained by Tramm and colleagues who showed that the surrounding non-neoplastic tissue does not affect the quantification of ESR1 , PGR , and ERBB2 mRNA expression in breast tumor samples [ 26 ]. The test results of the PAM50-based Prosigna breast cancer prognosis test, however, are affected by adjacent nontumor tissue.…”
Section: Discussionsupporting
confidence: 88%
“…From the 532 FFPE samples with sufficient tumor tissue, RNA extraction were performed and expression of ESR1, PGR, ERBB2 and MKI67 were quantified with quantitative real time polymerase chain reaction (described in detail in Supplementary Material, available online at http://www.informahealthcare.com [13,[25][26][27]). If the quantification failed, data from medical records and immunohistochemistry (IHC) was used to determinate ER-, PR-and HER2-status.…”
Section: Methodsmentioning
confidence: 99%